The modalities of use of medicinal flora in the province of Taza (Northern Morocco): Via an ethnobotanical and ethnopharmacological survey - Hajli, Faiza El; Chakir, Said; Ghabbour, Issam; Bouhraoua, Said; Kachmar, Mohamed Reda; Khabbach, Abdelmajid; Hammani, Khalil; Echchgadda, Ghizlane (Edelweiss Applied Science and Technology, 2024)
An ethnobotanical survey was carried out between April 2019 and April 2020 to verify the modalities of use of medicinal flora in the province of Taza. The main objective of this study is to determine the modalities of the use of medicinal flora using a survey questionnaire and quantitative analysis. An updated catalog of plants used in the Taza region will be produced at the end of the analysis. In the population studied, 59% are women and 52% are illiterate. 75 taxa are identified and grouped into 42 families, of which Lamiaceae (FUV=0.083) and Cupressaceae (FUV=0.068) are the most frequent. Criterion of Preparation (CP), Criterion of Part Used (CPU), and Criterion of Administration (CA) were calculated. Leaves are the most used part (60%), and the preparation of remedies is essentially based on decoctions (49%), and administration is mainly done orally (77%). The highest UV value was obtained for Rosmarinus officinalis L. (0.184), and Origanum compactum Benth. (0.184) and Thymus zygis L. (0.177). These same species also present the highest RFC. The highest FL value was obtained for 64 taxa. The highest ICF value was obtained for urinary/urological disorders (0.839) and metabolic diseases (0.831). Seven categories of diseases are treated and PCA analysis showed that PC1 accounted for 80.92% of the total variation while PC2 presented 13.86%, and PC1 is strongly influenced by FC, RFC, UV, and UR, while FL influences PC2. These results are considered to be a very important source of information for the study area and may help to prevent the loss of traditional knowledge on the use of medicinal plants